2017
DOI: 10.3389/feart.2017.00082
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Thickness of Thermal Aureoles

Abstract: Intrusions of magma induce thermal aureoles in the country rock. Analytical solutions predict that the thickness of an aureole is proportional to the thickness of the intrusion. However, in the field, thermal aureoles are often significantly thinner or wider than predicted by simple thermal models. Numerical models show that thermal aureoles are wider if the heat transfer in the magma is faster than in the country rock due to contrasts in thermal diffusivities or the effect of magma convection. Large thermal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…It is important to note when applying these experiments to natural environments with temperature fluctuations and cycles that repeated exposure to high temperatures may deviate from those of the single runs presented here due to hysteresis and the Kaiser affect (e.g., Yong & Wang, ; Lavrov, ; Heap, Lavallée, et al, ; Heap, Lavallée, et al, ). Additionally, the rate of temperature change in nature (thermal gradient) adjacent to magma bodies are highly spatially, and temporally variable (Annen, ). The rates used in this study are most applicable to areas within a few tens of meters of a magma body; however, we acknowledge that on average heating and cooling rates further from a magma body are likely to be much slower than our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note when applying these experiments to natural environments with temperature fluctuations and cycles that repeated exposure to high temperatures may deviate from those of the single runs presented here due to hysteresis and the Kaiser affect (e.g., Yong & Wang, ; Lavrov, ; Heap, Lavallée, et al, ; Heap, Lavallée, et al, ). Additionally, the rate of temperature change in nature (thermal gradient) adjacent to magma bodies are highly spatially, and temporally variable (Annen, ). The rates used in this study are most applicable to areas within a few tens of meters of a magma body; however, we acknowledge that on average heating and cooling rates further from a magma body are likely to be much slower than our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Both sample suites experience the greatest change in permeability at temperatures >550 °C, but the permeability of the highly altered andesite does not appear to be comparatively as affected as, or correlate as strongly with, increasing temperatures as the moderately altered andesite (Figure ). Thicknesses of alteration haloes are highly variable; are affected by magma type, local geology, and intrusion style; and are difficult to map due to poor exposure (e.g., Annen, ; Shanks, ). We therefore emphasize the importance of constraining the lithologies thermally stressed by geological processes or industrial development.…”
Section: Discussionmentioning
confidence: 99%
“…Dry rock has the highest temperature and water saturated rock the lowest. This means that convection of water lowered the temperature by~50 • C. It was concluded that diffusivity contrasts between magma and host rock and incremental sill emplacement had more effect on the aureole thickness than host-rock water content [84]. For the present study this implies that for highly porous and permeable lithologies (e.g., sandstone) the predicted time for cooling might be overestimated.…”
Section: Temperature Modelmentioning
confidence: 60%
“…Water convecting in the vicinity of sill intrusions could significantly modify the temperature and maturity effect of intrusions. Convection of hot fluids from the magma, the host-rock water, and decomposition products of kerogen is dependent on the permeability of porous host rocks or hydrofracturing in less porous host rocks (cf., [60,61,[82][83][84]. How the fluids from magma and host rock affect the fluid pressure and flow is determined by the host-rock porosity, permeability, and amount of fluids present [85].…”
Section: Temperature Modelmentioning
confidence: 99%
See 1 more Smart Citation